Comparison of Varying Corticosteroid Type, Dose, and Volume for the Treatment of Pain in Small‐ and Intermediate‐Size Joint Injections: A Narrative Review. Issue 7 (5th June 2019) - Cushman, Daniel M.; Ofek, Erika; Syed, Raafay H.; Clements, Nathan; Gardner, James E.; Sams, Jessica M.; Mulvey, Jade L.; McCormick, Zachary L.
Abstract : Objective: To systematically evaluate the scientific literature examining the effect of corticosteroid type, dose, and volume of small‐ and intermediate‐size joint injections on pain and function. Type: Narrative review. Literature Survey: Medline (PubMed), Cochrane Central Register of Controlled Trial, and SportDiscus databases were searched. Methodology: Inclusion criteria included prospective studies evaluating pain‐ and/or function‐related improvements following a corticosteroid injection of a small‐ or intermediate‐size joint. Synthesis: A total of 28 articles were included, all studying patients with osteoarthritis and/or rheumatoid arthritis. Eleven studies were randomized‐controlled trials comparing corticosteroid injections to a control treatment and three were randomized trials comparing corticosteroid dose or type; the rest were prospective case series without a control. Most studies used 10 to 20 mg of methylprednisolone or triamcinolone for small joints and 20 to 40 mg for intermediate joints; wrist joints were the only joint studied that directly compared doses—20 mg was noninferior to 40 mg. Triamcinolone hexacetonide was found to be superior to methylprednisolone in the interphalangeal finger joints in a single randomized‐controlled trial; no other studies compared steroid types in any joint. No studies evaluated the effect of volume on clinical outcomes. Conclusions: Very few studies directly examine the effect of corticosteroid type, corticosteroid dose, or injectate volume on clinical outcomes for small‐ or intermediate‐size joint arthralgia. Future studies are needed to better elucidate the most effective treatment protocols. Level of Evidence: IV.